PENDIDIKAN BUDI PEKERTI BERBASIS CERITA ANAK MELALUI PENANAMAN NILAI ETIS-SPIRITUAL DI SD - Edy Suryanto; Raheni Suhita; Yant Mujiyanto (Universitas Negeri Malang, 2015)
Abstract: the current study was intended to (1) find the model of character building for elementary school students, and (2) test the effectiveness of the character building model for elementary school students. The study utilized descriptive qualitative method. The data was collected by using observation, interview, document analysis, and test. The analysis technique of the interactive model and the product tryout were conducted by using experimental technique. The results of the study were (1) the early product development was prepared in such a way that the students would find the values by questioning and internalization processes through role playing, it would be meaningful if it was followed by making them habit in other relevant subjects, modeling, and giving examples; and (2) model could be used to effectively build the characters of the students in elementary schools. Abstrak: Penelitian ini bertujuan (1) menemukan model pendidikan budi pekerti untuk siswa SD, dan (2) menguji keefektifan model pendidikan budi pekerti untuk siswa SD. Penelitian menggunakan metode deskriptif-kualitatif. Pengumpulan data menggunakan terknik observasi, wawancara, analisis dokumen, dan tes. Teknik analisis model interaktif dan pengujian produk dengan teknik eksperimen. Hasil penelitian, (1) pengembangan awal model dikemas sampai pada tahap siswa menemukan nilai melalui pertanyaan-pertanyaan dan proses internalisasi melalui bermain peran, hal itu bermakna bila ditindaklanjuti dengan pembiasaan pada mata pelajaran lain yang relevan, pemodelan, dan keteladan; dan (2) model dapat digunakan untuk pembangunan karakter siswa secara efektif di SD.